ChemInform Abstract: Catalytic Synthesis of Fused 1, 4‐Dihydropyridines and 1, 4‐Dihydropyridine Derivatives Using Preyssler Heteropolyacids Catalyst. Issue 3 (22nd January 2013) - Gharib, Ali; Jahangir, Manouchehr; Roshani, Mina; Scheeren, J. W.
Abstract Heteropolyacid catalyzed Hantzsch dihydropyridine syntheses are described.